STUDI KELAYAKAN MAKAM KERAMAT AGUNG PEMECUTAN SEBAGAI DAYA TARIK WISATA PILGRIM DI DENPASAR (ANALISIS ASPEK PASAR DAN PEMASARAN) - Hudaningsih, Ashmi; Oka Karini, Ni Made; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata), 2014)
Makam Keramat Agung Pemecutan is one of the pilgrim tourism potentials in Denpasar. To avoid stagnant or decline position of Makam Keramat Agung Pemecutan development as a pilgrim tourist attraction, it is necessary to do a feasibility study. The most important and first aspect in feasibility study is market and marketing aspects.This study aims to determine the feasibility of market and marketing aspects of Makam Keramat Agung Pemecutan wich views from the market potential and the position of Makam Keramat Agung Pemecutan compared with its competitors, and make the right marketing strategy for Makam Keramat Agung Pemecutan in its development into a pilgrim tourist attraction. The results of this study shows that potential market of Makam Keramat Agung Pemecutan is domestic tourists who are Muslims. From the analysis of the competitive profile matrix shows Makam Keramat Agung Pemecutans position more competitive than its competitors. Therefore, Makam Keramat Agung Pemecutan is feasible on the market and marketing aspects. The suggestions provided are should establish management organization, make promotional activities, add facilities, and maintaining product quality of Makam Keramat Agung Pemecutan, continue this research about feasibility of Makam Keramat Agung Pemecutan in the other aspects especially culture aspect.
Keywords: Feasibility Study, Market Potential, Competitor Analysis, Pilgrim Tourist Attraction